Analysis of Elements in Innovation Communication of Liquid Organic Fertiliser - Mustapit Mustapit; Aryo Fajar Sunartomo; Sri Subekti; Diah Puspaningrum (UNIVERSITAS SEMBILANBELAS NOVEMBER KOLAKA, 2025)
Organic fertiliser has been widely used by farmers in Jember Regency, one of which is the type of liquid organic fertiliser (LOF) of local microorganisms. Research related to innovation adoption mostly focuses on innovation attributes. 4 other variables affect the speed of innovation adoption besides innovation attributes, namely: (1) type of innovation decision (choice, collective, or authoritarian), (2) communication channels (interpersonal or mass media), (3) social system (norms, degree of network relatedness), and (4) change agent (level of promotion effort). The purpose of this study was to analyse the elements in LOF innovation communication in Jember Regency with descriptive statistics, including: (1) relative profit level; (2) type of innovation decision; (3) communication channels; (4) social system; and (5) change agent. The research is a type of survey research with a quantitative method approach. The data analysis method in this study includes the following stages: (1) determination of scale values, and (2) descriptive statistical analysis. The results of the study showed that the elements in LOF innovation communication in Jember Regency generally show high achievements, so it can be concluded that LOF innovation has received support from farmers in Jember Regency. The elements of communication channels, social systems, and agents of change have achieved very high achievements, while the relative advantages element is already high, and the innovation decision type element is still moderate. Some things that need to be improved are decision-making at the farmer group level to be more democratic and prioritise deliberation. In addition, the relative advantages level can still be increased by overcoming technical constraints in LOF production and application.